Hadith #333 - Sahih al-Bukhari - Abu Juhaim Al-Ansari (Sahih al-Bukhari)
The Prophet (ﷺ) came from the direction of Bir Jamal. A man met him and greeted him. But he did not return back the greeting till he went to a (mud) wall and wiped his face and hands with its dust (performed Tayammum) and then returned back the greeting.
Grade: Sahih